Self assembled dual responsive micelles stabilized with protein for co-delivery of drug and siRNA in cancer therapy. (July 2017) - Aji Alex, M.R.; Nehate, Chetan; Veeranarayanan, Srivani; Kumar, D. Sakthi; Kulshreshtha, Ritu; Koul, Veena
Abstract: Design of safe and efficient vehicles for the combinatorial delivery of drugs and genetic agents is an emerging requisite for achieving enhanced therapeutic effect in cancer. Even though several nanoplatforms have been explored for the co-delivery of drugs and genetic materials the translation of these systems to clinical phase is still a challenge, mainly due to tedious synthesis procedures, lack of serum stability, inefficient scalability etc. Here in, we report development of reduction and pH sensitive polymeric graft of low molecular weight poly (styrene -alt -maleic anhydride) and evaluation of its efficacy in co-delivering drug and siRNA. The polymer was modified with suitable components, which could help in overcoming various systemic and cellular barriers for successful co-delivery of drugs and nucleic acids to cancer cells, using simple chemical reactions. The polymeric derivative could easily self assemble in water to form smooth, spherical micellar structures, indicating their scalability. Doxorubicin and PLK-1 siRNA were selected as model drug and nucleic acid, respectively. Doxorubicin could be loaded in the self assembling micelles with an optimum loading content of ∼8.6% w/w and efficient siRNA complexation was achieved with polymer/siRNA weight ratios >40. The polyplexes were stabilized in physiological saline by coating with bovine serum albumin (BSA). Stable drug loaded nanoplexes, for clinical administration, could be easily formulated by gently dispersing them in physiological saline containing appropriate amount of albumin. Drug release from the nanoplexes was significantly enhanced at low pH (5) and in the presence of 10 mM glutathione (GSH) showing their dual stimuli sensitive nature. In vitro cell proliferation assay and in vivo tumor regression study have shown synergistic effect of the drug loaded nanoplexes in inhibiting cancer cell proliferation. Facile synthesis steps, scalability and ease of formulation depict excellent clinical translation potential of the proposed nanosystem. Graphical abstract: